2020
DOI: 10.1101/2020.11.22.392217
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inferring a spatial code of cell-cell interactions across a whole animal body

Abstract: Cell-cell interactions are crucial for multicellular organisms as they shape cellular function and ultimately organismal phenotype. However, the spatial code embedded in the molecular interactions that drive and sustain spatial organization, and in the organization that in turns drives intercellular interactions across a living animal remains to be elucidated. Here we use the expression of ligand-receptor pairs obtained from a whole-body single-cell transcriptome of Caenorhabditis elegans larvae to compute the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 123 publications
0
17
0
Order By: Relevance
“…Ranks per Communicating Cell Types *2. Physical distance, measured by Euclidean distance between the closest cell types, was already reported to be an appropriate proxy of cell pair communication activity 65 . Other measures can be the neighbourhood enrichment or spatial co-occurrence of cells 24,66 .…”
Section: *1 Number Of Inferred Interactions Between Cell Clusters; Average Cell Inferencementioning
confidence: 99%
“…Ranks per Communicating Cell Types *2. Physical distance, measured by Euclidean distance between the closest cell types, was already reported to be an appropriate proxy of cell pair communication activity 65 . Other measures can be the neighbourhood enrichment or spatial co-occurrence of cells 24,66 .…”
Section: *1 Number Of Inferred Interactions Between Cell Clusters; Average Cell Inferencementioning
confidence: 99%
“…As we demonstrated here, OmniPath is able to deliver the input knowledge for different data analysis tools, such as CellPhoneDB (Efremova et al, 2020), NicheNet (Browaeys et al, 2019), CellChat (Jin et al, 2021), ICELLNET (Noël et al, 2021), NATMI (Hou et al, 2020), cell2cell (preprint: Armingol et al, 2020a), and CARNIVAL (Liu et al, 2019) to infer communication between (Armingol et al, 2020b) and within cell types. For some of the analysis tools, we provide dedicated software integration and workflows (https://workflows.omnipathdb.org/).…”
Section: Discussionmentioning
confidence: 98%
“…For instance, our strategy can be readily applied to time series data by considering time points as the contexts, and to spatial transcriptomic datasets, by previously defining cellular niches or neighborhoods as the contexts. Moreover, we have also included Tensor-cell2cell as a part of our previously developed tool cell2cell 60 , enabling previous functionalities such as employing any list of LR pairs (even including protein complexes), multiple visualization options, and personalizing the communication scores to account for other signaling effects such as the (in)activation of downstream genes in a signaling pathway 23,61 , which could lead to different biological interpretations 57 . Lastly, we demonstrated that Tensor-cell2cell stands as a fast, low-memory and accurate method (Figure 3), which can be substantially accelerated when a GPU is available (Figure 3a).…”
Section: Discussionmentioning
confidence: 99%
“…Tensor-cell2cell is implemented in our cell2cell suite 65 , which is available in a GitHub repository (https://github.com/earmingol/cell2cell). All the code and input data used for the analyses are available online in a Code Ocean capsule for reproducible runs (https://doi.org/10.24433/CO.0051950.v2).…”
Section: Code and Data Availabilitymentioning
confidence: 99%